A Correlational Study on Teachers' Occupational Stress, Job Anxiety, Personality Dimensions and Performance (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
This study determined the correlations between occupational stress, job anxiety, personality dimensions and instructional competence of elementary teachers. The study employed the descriptive-correlational research design. There were 161 respondents composed of different teachers from small and big schools in the District of Los Banos, Laguna. The study utilized standardized questionnaires to assess the Occupational Stress, Job Anxiety, Personality Dimensions, and Instructional Competence of Elementary Teachers. The data gathered were treated using Mean, Standard Deviation, and ANOVA. The findings revealed that occupational stress has a significant relationship with the teacher's competence in terms of communicative competence. However, occupational stress has no significant relationship between the teacher's competence in terms of instructional competence and social skills. The result also shows that there is a significant relationship between job anxiety in terms of recognition and teacher's competence in terms of instructional competence. However, there is no significant relationship between job anxiety in terms of recognition and teacher's performance in terms of communicative competence and social skills. Similarly, there is a significant relationship between job anxiety in terms of self-esteem and teacher's competence in terms of instructional and communicative competence. However, there is no significant relationship between job anxiety in terms of self-esteem and teacher's competence in terms of social skills. Lastly, the result shows that there is no significant relationship between job anxiety in terms of security, human relations at work, rewards and punishment, future prospects and capacity for work, and teacher's performance in terms of instructional competence, communicative competence, and social skills.